Estudos sobre a intercalação dos corantes azul brilhante-FCF e azul de coomassie G-250 em ácido desoxirribonucléico (DNA) - Queiroz, Carmen Fabiola Otoni de (2007)
This work turns on the process of intercalation of two types of dyes in DNA, the Brilliant Blue FCF, an food dye and the Coomassie Blue G-250, that is habitually used in biochemists assays. Data gotten through assays of the spectroscopy of absorption in the region of the UV/Vis and of infrared with regard to the complex formed between DNA/ Brilliant Blue show an effective interaction between Brilliant Blue FCF and the DNA, strengthening the possibility of the dye to be intercalating enter the bases of the DNA, occupying mainly the site of guanine. So excellent alterations in the absorptions with regard to the formed complex had not been observed enter the DNA/Coomassie Blue. We can conclude that the Coomassie Blue G-250 can be binding through electrostatic interaction in the surface of the DNA, that is, binding to the phosphate groups.